Hermeneutics and Semiosis in the Intersubjective Network of Nostalgia - Hernández Carmona, Luis Javier (Rastros Rostros, 2012)
This paper originates from the research “The Ontosemiotic as Methodological Perspective in Literary Studies” of 2011, funded by the Council of Scientific, Humanistic, Technology and Arts Development (cdchta) at the Universidad de Los Andes, Venezuela, under the code NURR-H-516-11-06-B. This research proposed nostalgia as cultural isotopy within the archetypes of an individual/collective memory, logos shown in the intimacy, which is made a dynamic object by ontosemiotic analysis. From the interrelation of discourses centered on the being that states them and the interacting production modes in this complex process in which the discourses are linked to dynamic interpretations of the significant objects, creating new naturalizations that constitute our idea of reality, and require dissimilar signs of approach supported by new dynamic interpreters.
Keywords: intersubjectivity; isotopy; nostalgia; ontosemiotic; signification